Analisis Perbandingan Sistem Inferensi Fuzzy Mamdani Dan Fuzzy Sugeono Dalam Menentukan Siswa Terbaik - Helmi Fauzi Siregar; K Kartika (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
In the process of selecting the best students, there are several indicators that are also important factors that is grades, absenteeism, academic and non-academic achievements. The purpose of this study is to be able to apply an information system comparison application in determining the best students at SMA Negeri 1 Aek Kuo. The data used in this study are student data, test score data, attendance attendance data and academic and non-academic achievement data. The results of the assessment obtained have the same decision results, from this test it can be seen that the calculation results of a student with the highest score using the Mamdani method are Tira Dwi Fitri Br Naibaho with a score of 70 while the Sugeno method is Tira Dwi Fitri Br Naibaho with a value of 39. This application later it can be accessed online and can be accessed anywhere and anytime